Primary small intestine mesenteric low-grade fibromyxoid sarcoma with foci of atypical epithelioid whorls and diffuse DOG1 expression: a case report - Jialing Huang; Steven Cohen; Gerorge Jour (BMC, 2020)
Abstract Background Low-grade fibromyxoid sarcoma (LGFMS) is a rare fibroblastic tumor often involving deep tissue of trunk and lower extremities in young to middle-aged patients. Rarely, LGFMS can occur in other sites including head and neck, chest, abdomen and female reproductive system. Three cases of LGFMS in mesentery of small intestine have been reported and all have conventional histologic features. Herein we reported a unique case of LGFMS in mesentery of small intestine. Case presentation A 43 year-old male with chief complaint of lower back pain for 4 years presented to our hospital. Physical exam reveal a firm, non-tender, non-distended, mobile large abdominal mass, which was shown on abdominal CT as a 10 cm retroperitoneal tumor. Biopsy revealed a spindle cell neoplasm in a myxoid background with a delicate vascular network. Tumor resection was performed. Gross examination of the resected specimen showed a 10.8 cm, tan-white, smooth, firm, lobulated mesenteric mass with bulging and gelatinous cut surface and confined within small bowel serosa. Microscopic examination demonstrated foci epithelioid cords and whorls with prominent atypia, in additional of regular, bland-appearing spindle cells in a fibrous and myxoid stroma and osseous metaplasia. The tumor cells stained diffusely positive for DOG1 with moderate staining density, and diffusely and strongly positive for MUC4. Rearrangement involving FUS (16p11.2) gene was identified with break-apart probe and confirmed by Anchored Multiplex PCR. A final diagnosis of low-grade fibromyxoid sarcoma was rendered. Conclusion Our case highlights the importance of including LGFMS in the differential diagnosis of mesenteric tumors and the DOG1 positivity which could represent a potential diagnostic pitfall.